Application of Zero-Dimensional Nanomaterials in Biosensing - Wang, Zhengdi; Hu, Tingting; Liang, Ruizheng; Wei, Min (Frontiers in Chemistry, 2020)
Zero-dimensional (0D) nanomaterials, including graphene quantum dots (GQDs), carbon quantum dots (CQDs), fullerenes, inorganic quantum dots (QDs), magnetic nanoparticles (MNPs), noble metal nanoparticles, upconversion nanoparticles (UCNPs) and polymer dots (Pdots), have attracted extensive research interest in the field of biosensing in recent years. Benefiting from the ultra-small size, quantum confinement effect, excellent physical and chemical properties and good biocompatibility, 0D nanomaterials have shown great potential in ion detection, biomolecular recognition, disease diagnosis and pathogen detection. Here we first introduce the structures and properties of different 0D nanomaterials. On this basis, recent progress and application examples of 0D nanomaterials in the field of biosensing are discussed. In the last part, we summarize the research status of 0D nanomaterials in the field of biosensing and anticipate the development prospects and future challenges in this field.